Description of the final instar larva of Pseudagrion pruinosum (Burmeister, 1839) (Odonata: Coenagrionidae) from Thailand - Saetung, Tosaphol; Boonsoong, Boonsatien (Zootaxa, 2016)
Herein the final instar larva of Pseudagrion pruinosum (Burmeister, 1839) is described and illustrated for the first time, based on reared specimens from Thailand. When compared with the other known Pseudagrion larvae, P. pruinosum is distinguished by three setae on the labial palp, five teeth on the truncate, denticulate lobe on the distal marginal end of the labial palp, one premental seta and a row of three minute setae on each side of the midline, as well as shape and tracheation of caudal gills.